Children born with low weight: what factors interfere with their growth? - Regis de Oliveira Santos, Lucas; Nery Teixeira Palombo, Claudia; Maria Carneiro Oliveira, Marcia; Javier Avendano Vasquez, Carlos (Seven Editora, 2023)
Introduction: It is known that the state of health at birth is a determining factor of greater importance for the survival and quality of life of the child. Children born with less than 2500 grams are more likely to die in the first months of life, have delays in neuro-psychomotor development, and have chronic non-communicable diseases in adulthood. As the growth process depends on the interaction between genetic load and factors extrinsic to the human being, knowing which factors interfere in the growth of children born with low weight can contribute to qualifying the child’s health care. Objective: To identify in the kinetic literature the factors that interfere with the growth of children born with low weight up to two years of life. Method: The proposed systematic review was conducted according to the methodology of the Joanna Briggs Institute for systematic reviews of etiology and risk. Only studies that quantitatively addressed the factors that interfere with the growth of children born with low weight up to 2 years of age were selected. Studies involving children with congenital or perinatal pathology did not participate in this review. The data were extracted by the principal investigator and included: the author/year, objective, method, and main results of the study. Results: Of the 3433 articles identified, only 1 2 studies were included in this review. Diet, socioeconomic status, family-centered care, and genetics were identified as the main factors of interference in the growth of children born with low weight up to two years of age. Conclusions: The growth of children born with low weight is determined by several factors, especially diet and socioeconomic aspects. DOI: https://doi.org/10.56238/devopinterscie-104